2018
DOI: 10.22159/ajpcr.2018.v11i3.23531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticle-Mediated Wound Therapy on Biochemical, Hematological, and Histological Parameters

Abstract: Methods: Extraction of Syzygium cumini was done and was used for silver nanoparticle synthesis. The synthesized nanoparticles were characterized by ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy, which confirms the availability of nanosilver particles with marginally spherical morphology. The particles were then carried forward for treating impaired diabetic wounds in Wistar rat models. Regular photography was done a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(46 reference statements)
0
4
0
1
Order By: Relevance
“…The results obtained showed efficient wound healing potential of silver nanoparticles as compared to pre-existing drug povidone-iodine, i.e., the percentage reduction in wound area after therapy was 100% on day 14 th day in case of biosynthesized silver nanoparticle(CPAgNP) treated group, 92.39% reduction in AECPL treatment group, 95.89% reduction in case of povidone-iodine-treated animals, 80.67% reduction in case of diabetic control group (diabetic) and 87.67% reduction in healthy control group (non-diabetic). Chauhan et al, (2018) also reported efficient wound healing (96.9%) potential of biosynthesized silver nanoparticles as compared to drug povidone-iodine (64.28%).…”
Section: Wound Healing Measurementsmentioning
confidence: 86%
“…The results obtained showed efficient wound healing potential of silver nanoparticles as compared to pre-existing drug povidone-iodine, i.e., the percentage reduction in wound area after therapy was 100% on day 14 th day in case of biosynthesized silver nanoparticle(CPAgNP) treated group, 92.39% reduction in AECPL treatment group, 95.89% reduction in case of povidone-iodine-treated animals, 80.67% reduction in case of diabetic control group (diabetic) and 87.67% reduction in healthy control group (non-diabetic). Chauhan et al, (2018) also reported efficient wound healing (96.9%) potential of biosynthesized silver nanoparticles as compared to drug povidone-iodine (64.28%).…”
Section: Wound Healing Measurementsmentioning
confidence: 86%
“…Further the hematological parameters such as hct, PLT, RBC, WBC count etc. did not have much variation during Ag NP application [79]. Plant based nanoparticles can also control the inflammatory response by downregulating TNF-α, IL-6, IL-1β, and IL-10 synthesis by the cells and sometimes can control inflammatory pathways by inhibiting NF-kB [53].…”
Section: Green Synthesized Nanoparticlesmentioning
confidence: 96%
“…In 2017, Peng et al reported that the surface stabilization of NPs with low molecular weight stabilizers decreased the absorption characteristics in the body, making it less toxic in an MRSA-infected mouse wound model [ 229 ]. Likewise, the biosynthesis of NPs has showcased on repeated occasions its non-toxic abilities without losing its antibacterial, antibiofilm and wound-healing integrity [ 169 , 230 , 231 ]. As nanoengineering is itself an evolutionary process that requires the amalgamation of several subunits, there is always room for improving the mode of application.…”
Section: Nanotechnology In Regenerationmentioning
confidence: 99%